Transparansi dan Akuntabilitas Transparansi dan Akuntabilitas Dalam Proses Pengadaan Barang dan Jasa di Dinas Komunikasi dan Informatika Kabupaten Bogor - Yuliarti, Erni; Arief Tri Hardiyanto; Hendro Sasongko (International Journal Administration, Business & Organization, 2026)
Based on the Supreme Audit Agency (BPK) report, procurement of goods and services in Bogor Regency still faces challenges, including limited public information access and weak independent oversight. These issues contributed to the regional government’s Qualified Opinion (WDP), driven by unclear management of BOS-related expenditures, non-compliant allowance for doubtful accounts, and high short-term liabilities. This study analyzes the implementation of transparency and accountability principles in the procurement process at the Department of Communication and Informatics of Bogor Regency. Using a qualitative descriptive approach, data were collected through open and closed questionnaires, in-depth interviews, and document analysis, and analyzed using the Miles and Huberman interactive model. The findings indicate that transparency through the Electronic Procurement Service (LPSE) system has been implemented adequately; however, challenges persist in data integration, documentation quality, and internal monitoring. Accountability efforts through reporting and auditing are evident but constrained by limited human resource competence, the absence of measurable accountability mechanisms, and weak multi-layered oversight. The study underscores the need for integrated digital data management, capacity building for procurement personnel, and stronger oversight systems to enhance transparency and accountability in public procurement.